SOSIALISASI METODE PEMBELAJARAN UNTUK MENINGKATKAN KAPASITAS GURU PENDIDIKAN AGAMA ISLAM DAN ISMUBA SE KABUPATEN KUANTAN SINGINGI - Ritonga, Mahyudin; Lahmi, Ahmad; Rasyid, Aguswan; Bakar, Rohandi Abu; Sukri, Indra (Universitas Muhammadiyah Tapanuli Selatan, 2021)
The capacity of teachers is part of the requirements to realize the educational goals that have been set, it can be affirmed that if teachers do not have adequate capacity then the expectation to realize the goals of education is very minimal. Therefore, this activity is designed to provide information to teachers in the PDM Kuantan Singingi environment about strategies that can be done to realize themselves as teachers who have the capacity. This devotional activity involves various parties in accordance with their respective tupoksi. The result of this activity is that through the day seminar activities pai and ISMUBA teachers have comprehensive knowledge related to strategies to increase capacity as teachers. This is said because the material submitted relates to the necessity of a teacher to have conceptual and practical knowledge related to learning methods, teaching materials, utilization of information technology and evaluation of learning.